Unmasking The Failure of Multiculturalism in The Kite Runner by Khaled Hosseini - Ula, Fadhila Maghfirotul; Anam, Zuhrul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research investigates the issue of multiculturalism in Khaled Hosseini's novel The Kite Runner (2003). The novel narrates the friendship, betrayal, and redemption between two boys (Amir, who is from the Pashtun tribe, and Hassan, who is from the Hazara tribe) in Afghanistan, separated by social backgrounds and traumatic incidents. This research applies the Hybridity theory proposed by Homi K. Bhabha (1994), an Indian literary theorist and professor recognized for his contributions to postcolonial studies. A qualitative method is preferred as textual analysis heavily permeates the research. The main objective of this research is to center on Hosseini's presentation of the main characters in the novel, Amir and Hassan in the context of multiculturalism's failure in Afghanistan. The findings illustrate that the failure of multiculturalism between the Pashtun and Hazara tribes in the novel encounters challenges which include discrimination, persecution & violence, and systemic injustices. Efforts such as Building Inter-Ethnic Friendship and Solidarity and Against Discrimination and Injustice to overcome the failure of multiculturalism between Pashtuns and Hazaras fail due to the complexity of structural factors, limited access to healthcare and education, the persistence of violence and discrimination, differences in values and culture, and stereotypes and social practices in Afghan society.